Investigating the effect of Corporate Social Responsibility and affective commitment on Corporate Performance in Oil and Gas Corporations in Yemen - Alsamawi, Mohamed Abdulwali Ali; Mohd Ridzuan, Darun; Panigrahi, Shrikant; Al-Refaei, Abd Al-Aziz Hamed (Akademia Baru, 2019)
This article investigates the effect of corporate social responsibility (CSR) and affective commitment on corporate performance. Although the social and political issues are the root cause of the threat to sustainability development in the world, only corporations have the three essential components, namely resources, global reach and motivation, in order to achieve sustainability. From the economic distress and social challenges that Yemen is facing, it is very important to understand the complex connection and interdependence of CSR activities. Data were collected by means of self-administered survey questionnaire. A total of 339 usable responses were obtained from the employees working in three major oil and gas corporations in Yemen. The findings revealed that affective commitment influence corporate performance by 0.176 at significant level of 0.05. The study result shows that CSR to employee dimensions play an important role in nurturing the commitment of the employees, their engagement and innovation. Corporate can achieve long term growth followed with maintaining effective CSR activities and achieve its reputation with an effective CSR strategies.